Polymer based microneedle patch fabricated using microinjection moulding - Pattanaphong Janphuang; Mongkhol Laebua; Chanwut Sriphung; Phatsakon Taweewat; Anan Sirichalarmkul; Kasiphisan Sukjantha; Napatporn Promsawat; Pimchanok Leuasoongnoen; Somphong Suphachiaraphan; Kantapon Phimol; Don Isarakorn; Somchai Tancharakorn (My University, 2018)
This paper presents the development of a polymer based microneedle patch for transdermal drug delivery application using plastic microinjection moulding. Design and analysis of the microneedle cavities and mould insert used in the injection moulding process were carried out using Computer-Aided Engineering (CAE) software. A mould insert with low surface roughness was fabricated using Micro Electrical Discharge Machining (μ-EDM). The injection moulding parameters including clamping force, temperature, injection pressure and velocity were characterized in order to obtain the optimum reproducibility. Solid truncated cone microneedles, made of biocompatible polymethyl methacrylate (PMMA), with a round tip radius of 50 μm and 500 μm in height have been realized by microinjection moulding process demonstrating the potential of a low cost, high production efficiency, and suitable for mass production. In addition, a mould insert of cylindrical microneedles fabricated using X-ray LIGA has been proposed.
Keywords: Injection moulding; Insert (composites); Advancements in Transdermal Drug Delivery